The usage of Escape Rooms in English Class as a Playful Approach to Active Learning Vocabulary - Quizhpe Castro, Briggette Alexandra (2024)
The objective of this study is to demonstrate how the implementation of Escape Rooms in the teaching of English vocabulary can promote active learning and improve students' mastery of said vocabulary. To achieve this objective, a mixed approach methodology was used that combined qualitative and quantitative elements. A pre-test was carried out to diagnose the students' initial level of knowledge regarding vocabulary. Then, Escape Rooms were implemented as a recreational method for a certain period. Finally, the effectiveness of this strategy was evaluated through a post-test. The results of the study indicate that the implementation of Escape Rooms in the English class had a significantly positive impact on students' vocabulary learning. Scores on the post-test showed a notable increase compared to the pre-test, suggesting that this playful strategy promoted better vocabulary comprehension and retention. In conclusion, this study demonstrates that the use of Escape Rooms as a playful approach in teaching English vocabulary is highly effective in promoting active learning and improving students' mastery of vocabulary. This strategy not only led to a significant increase in grades, but also encouraged student engagement and interest in the learning process, underscoring the importance of active and experiential teaching in the language classroom